Inovasi Gamifikasi Pada Pembelajaran Matakuliah Pengembangan Media Sederhana - Diana Ariani; Dewi s. Prawiradilaga; Wasetya Fatharani; R. A. Hirmana Wargahadibrata (Jurnal Pembelajaran Inovatif, 2022)
Learning activities with fully online learning during the pandemic caused student saturation in carrying out learning routines. Especially on less desirable materials. For this reason, learning innovations are needed to facilitate student learning needs, one of which is gamfication. This study aims to produce Gamification in Pengembangan Media Sederhana course at the Education Technology Study Program, State University of Jakarta. Study. This development research follows the Rapid Prototyping model procedure by Tripp and Bichelmeyer, which has 5 stages, namely Assess Needs and Analyze Content, Set Objectives, Construct Prototype (design), Utilize Prototype (research), and Installing and Maintain System. Evaluation with an open survey obtained user interest with high gamification, and more adjustments are needed in the elements used. Abstrak Kegiatan pembelajaran dengan fully online learning selama masa pandemi menyebabkan kejenuhan pada mahasiswa dalam melaksanakan rutinitas pembelajaran. Terlebih pada materi yang kurang diminati. Untuk itu perlu inovasi pembelajaran dalam memfasilitasi kebutuhan mahasiswa belajar, salah satunya dengan Gamfikasi. Penelitian ini bertujuan menghasilkan Gamifikasi pada matakuliah Pengembangan Media Sederhana di Program Studi Teknologi Pendidikan Universitas Negeri Jakarta. Penelitian. Penelitian pengembangan ini mengikuti prosedur model Rapid Prototyping oleh Tripp dan Bichelmeyer, yang memiliki 5 tahap, yaitu Assess Needs and Analyze Content, Set Objectives, Construct Prototype (design), Utilize Prototype (research), dan Installing and Maintain System. Evaluasi dengan survey terbuka diperoleh minat pengguna dengan gamifikasi yang tinggi, dan perlu penyesuaian lebih dalam elemen-elemen yang digunakan.